2020
DOI: 10.3390/jmse8040238
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Decreased pH and Caffeine Affects Hemocyte Parameters in the Mussel Mytilus galloprovincialis

Abstract: Combined effects of reduced pH, as predicted under climate change scenarios, and the most popular and widely used stimulant caffeine were assessed in hemocyte parameters of the mussel Mytilus galloprovincialis, being hemocytes involved in immune defense. Bivalves were exposed for one week to natural pH (8.1) and two reduced pH values (pH −0.4 units and pH −0.7 units). Exposure continued for additional two weeks, both in the absence and in the presence of environmentally relevant concentrations of caffeine (0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…This absence of antioxidative responses and lipid destabilisation is in opposition to the results published on Mytilus californianus (mussels) which revealed induction of HSP70 in gills after caffeine exposure (0.05 and 0.2 µg/L for 10, 20 and 30 days) [ 7 ]. In Mytilus galloprovincialis, alteration of haemocyte parameters (total haemocyte count, haemocyte volume and diameter, proliferation) was noted after 14 or 21 days due to the combined effects of pH reduction (8.1 to 7.7 or 7.4) and caffeine exposure (0.05 and 0.5 µg/L) [ 40 ]. A dose-dependent reduction in haemocyte lysosomal membrane stability was also noted in Ruditapes philippinarum after 14 days of caffeine exposure (range: 1–50 µg/L) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This absence of antioxidative responses and lipid destabilisation is in opposition to the results published on Mytilus californianus (mussels) which revealed induction of HSP70 in gills after caffeine exposure (0.05 and 0.2 µg/L for 10, 20 and 30 days) [ 7 ]. In Mytilus galloprovincialis, alteration of haemocyte parameters (total haemocyte count, haemocyte volume and diameter, proliferation) was noted after 14 or 21 days due to the combined effects of pH reduction (8.1 to 7.7 or 7.4) and caffeine exposure (0.05 and 0.5 µg/L) [ 40 ]. A dose-dependent reduction in haemocyte lysosomal membrane stability was also noted in Ruditapes philippinarum after 14 days of caffeine exposure (range: 1–50 µg/L) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have suggested that toxicity causes significant alterations in hemocyte counts in mussels, and it can be considered a potential biomarker to access environmental health [ 60 , 61 ]. Hemocyte counts significantly reduced when Mytilus coruscus was treated with titanium dioxide for 35 days [ 42 ], and when Mytius edulis was exposed to cadmium for 7 days [ 62 ]. Cellular abnormalities and impaired counts were recorded in the zebra mussel Dreissena polymorpha in response to cadmium toxicant [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample hemolymph was then fixed in a similar volume of Alsevier solution (MP Biomedicals, Solon, OH, USA) formulated by putting 3% formaldehyde [ 41 ]. The hemocyte concentration was quantified through the hemocytometry approach as described by Munari et al [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Here, organisms can be exposed to a wide range of anthropogenic substances, including emerging contaminants with unknown environmental impacts, an aspect that raises increasing concern [16,17]. Laboratory and mesocosms experiments were carried out to test if OA can exacerbate the negative effects of different pollutants in several marine calcifying species including bivalves [18][19][20][21][22][23][24], echinoderms [25][26][27], and polychaetes [28][29][30] at both adult and larval stage. On the contrary, the effects of OA in combination with aquatic pollutants on gametes are still poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high consumption, the environmental occurrence, and in the case of PFOS also the persistency of these contaminants being well documented, their effects on aquatic organisms need to be investigated more deeply also in relation to the ongoing climate change. Regarding DFC and CAF, it was already observed in other marine invertebrates that their presence at environmentally relevant concentrations can exacerbate OA effects on several physiological parameters at different life stages [20][21][22][23][24] but specifically not on sea urchins' sperm performances. Regarding PFOS instead, it is completely unknown the combined effects that PFOS and reduced pH can have in any marine invertebrate species.…”
Section: Introductionmentioning
confidence: 99%